Some Comments on the History of Socio-Economic and Ethno-Cultural Relations During the Eneolithic Period of Central Asia " - Kuvonchbek, Bobokhanov (European Journal of Life Safety and Stability (2660-9630), 2022)
The article examines the history of the development of socio-economic and cultural-ethnic relations of the Central Asian Eneolithic society.